Test–retest reproducibility of human brain multi‐slice 1H FID‐MRSI data at 9.4T after optimization of lipid regularization, macromolecular model, and spline baseline stiffness. Issue 1 (21st September 2022) - Ziegs, Theresia; Wright, Andrew Martin; Henning, Anke
Abstract : Purpose: This study analyzes the effects of retrospective lipid suppression, a simulated macromolecular prior knowledge and different spline baseline stiffness values on 9.4T multi‐slice proton FID‐MRSI data spanning the whole cerebrum of human brain and the reproducibility of respective metabolite ratio to total creatine (/tCr) maps for 10 brain metabolites. Methods: Measurements were performed twice on 5 volunteers using a short TR and TE FID MRSI 2D sequence at 9.4T. The effects of retrospective lipid L2‐regularization, macromolecular spectrum and different LCModel baseline flexibilities on SNR, FWHM, fitting residual, Cramér‐Rao lower bound, and metabolite ratio maps were investigated. Intra‐subject, inter‐session coefficient of variation and the test–retest reproducibility of the mean metabolite ratios (/tCr) of each slice was calculated. Results: Transversal, sagittal, and coronal slices of many metabolite ratio maps correspond to the anatomically expected concentration relations in gray and white matter for the majority of the cerebrum when using a flexible baseline in LCModel fit. Results from the second measurements of the same subjects show that slice positioning and data quality correlate significantly to the first measurement. L2‐regularization provided effective suppression of lipid‐artifacts, but should be avoided if no artifacts are detected. Conclusion: Reproducible concentration ratio maps (/tCr) for 4 metabolites (total choline, N‐acetylaspartate, glutamate, and myoinositol) spanning the majority of the cerebrum and 6 metabolites (N‐acetylaspartylglutamate, γ‐aminobutyric acid, glutathione, taurine, glutamine, and aspartate) covering 32 mm in the upper part of the brain were acquired at 9.4T using multi‐slice FID MRSI with retrospective lipid suppression, a macromolecular spectrum and a flexible LCModel baseline.